Advancing circular economy performance through blockchain adoption: A study using institutional and resource-based frameworks - Subhodeep Mukherjee; Rashmi Ranjan Panigrahi; Ruchi Sharma; Avinash K Shrivastava (Sustainable Futures)
Circular economy (CE) and blockchain technology (BCT) are emerging concepts that can impact the performance of firms. The transition to a CE is a requirement for organizations to achieve sustainable development and reduce carbon footprints. This study empirically validated the adoption of BCT for improving the CE performance through institution and resource-based theories. The data is collected from the 307 respondents who are employees working in Micro, Small, and Medium-Sized Enterprises (MSMEs) using a structured questionnaire. The respondents have the required educational qualifications and work experience. According to our results, coercive, normative, and mimetic pressure positively correlated with tangible resources and workforce skills. Also, tangible resources and workforce skills found a positive relationship in adopting BCT. Lastly, adopting BCT was identified as the reason for increased CE performance. The findings of this study will contribute to CE performance in MSMEs. It will help identify various practices contributing to the CE's performance. The prior research has not utilized institution- and resource-based theories to adopt BCT, which has impacted CE performances. This study is one of the few research works which measured the CE performance using BCT adoption under the theoretical lens of institutional and resource-based theory. The current limitations of the study are the sample size and data collected from a developing country perspective.